Peer learning in an undergraduate linear Algebra course - A social network analysis - THULASIDAS, Manoj (Institutional Knowledge at Singapore Management University, 2023)
This study employs Social Network Analysis (SNA) to explore peer learning behaviors among undergraduate Linear Algebra students. By examining the relational dynamics within the classroom, SNA unveils patterns of interaction, information flow, and collaboration among students. Our analysis identifies the prevalence and evolution of peer learning, and how it influences the students' academic performance. It also unveils the attributes of the students who engage in peer helping and the formation of small communities through such interactions. The findings of the study can provide valuable insights for educators aiming to enhance peer learning and improve educational practices in Linear Algebra and other fundamental subjects, thereby contributing to curriculum development and educational reforms.